Comparative effectiveness of physical activity interventions on cognitive functions in children and adolescents with Neurodevelopmental Disorders: a systematic review and network meta-analysis of randomized controlled trials - Ruiyuan Tao; Yijian Yang; Mark Wilson; Jeremy R. Chang; Chang Liu; Cindy H. P. Sit (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Physical activity (PA) interventions have been shown to yield positive effects on cognitive functions. However, it is unclear which type of PA intervention is the most effective in children and adolescents with Neurodevelopmental Disorders (NDDs). This study aimed to compare the effectiveness of different types of PA interventions on cognitive functions in children and adolescents with NDDs, with additional analyses examining intervention effects across specific NDD types including attention-deficit/hyperactivity disorder (ADHD) and autism spectrum disorder (ASD). Methods In this systematic review and network meta-analysis, seven databases (Web of Science, PubMed, Medline, APA PsycINFO, Embase, CINAHL, and SPORTDiscus) for randomized controlled trials from database inception to September 2023 were searched. Randomized controlled trials comparing the effectiveness of PA intervention with any non-pharmacological treatment or control group on cognitive functions in children and adolescents diagnosed with NDDs aged 5–17 years were included. Frequentist network meta-analyses were performed based on standardized mean differences (SMD) using random effects models to examine post-intervention differences in cognitive functions, including attention, memory, and executive functions. Intervention dropout was assessed as a measure of treatment acceptability. Results Thirty-one randomized controlled trials (n = 1,403, mean age 10.0 ± 1.9 years) with 66 arms were included in the network. Mind-body exercise (MBE; SMD = 1.91 for attention; 0.92 for executive functions), exergaming (SMD = 1.58 for attention; 0.97 for memory; 0.94 for executive functions), and multi-component physical activity (MPA; SMD = 0.79 for executive functions) were associated with moderate to substantial cognitive improvements compared with usual care, whereas the effectiveness of aerobic exercise (AE) was non-significant. Exergaming (SMD = 0.78, 95%CI 0.12 to 1.45) and MPA (SMD = 0.64, 95%CI 0.11 to 1.18) were more effective than AE for executive functions. When analyzing specific NDD types, exergaming lost its superiority over usual care for attention and memory in ADHD, nor for executive functions in ASD. Instead, MPA demonstrated significant benefits across these domains and populations. The certainty of evidence for these comparisons was very low to low. No significant differences in acceptability were observed among MBE, exergaming, and MPA. Conclusions The findings in this study suggest that MBE, exergaming, and MPA were effective interventions for improving domain-specific cognitive functions in children and adolescents with NDDs. AE demonstrated non-significant effectiveness for all outcomes. MBE emerges as particularly advantageous for attention. MPA yielded consistent improvements in memory and executive functions across NDD types. Further high-quality randomized controlled trials of direct comparisons are needed to confirm and expand on the findings from this NMA. Trial registration PROSPERO CRD42023409606.